Primary Pancreatic Lymphoma: A Rare Clinical Entity - Hiba Siddiqui (ziauddin University, 2024)
Pancreatic adenocarcinoma is one of the most aggressive malignant diseases, rarely, pancreatic lymphomas are diagnosed. The final diagnosis of primary pancreatic lymphoma demands histopathology of the lesion; however, radiological features and tumor markers can help to give an idea about the disease. The most important difference between primary pancreatic lymphomas and pancreatic adenocarcinoma is the different treatment modalities the response to treatment and finally good prognosis in primary pancreatic lymphoma cases. Clinically it is difficult to differentiate the symptoms of primary pancreatic lymphomas from other carcinomas of the pancreas. Rarely patients may experience B- symptoms of lymphomas that are night sweats and fever in the case of primary pancreatic lymphomas.